Comparison of Clinical and Demographic Features of FMF with Sacroiliitis Patients with FMF and Axial Spondyloarthritis Patients - Bayrak, Esra Dilşat; Erten, Sukran; Kucuksahin, Orhan; Ersoy, Osman (Aktuelle Rheumatologie, 2020)
Objectives Familial Mediterranean fever (FMF) is the most common autoinflammatory disease, characterised by recurrent fever and serositis attacks lasting 1–3 days. Musculoskeletal involvement is the second most common manifestation in FMF patients. Sacroiliitis is another musculoskeletal involvement; as there is no spinal involvement, this is called FMF with sacroiliitis. This study was designed to investigate the clinical, demographic and genetic features of FMF in sacroiliitis patients and to compare them with axial SpA and FMF patients.Materials and Methods Forty-two FMF with sacroiliitis patients, 100 axial SpA patients and 100 FMF patients were recruited, and their demographic characteristics were recorded. Evidence of sacroiliitis was confirmed by sacroiliac joint MRI, and patients were examined for arthritis and enthesitis. MEFV gene mutations, HLA B27 positivity and ESR and CRP results were compared.Results In the FMF with sacroiliitis group, the M694V mutation was detected in 59.5% of patients. FMF with sacroiliitis patients were largely (83.3%) negative for HLA B27. The frequency of enthesitis was similar between FMF with sacroiliitis and axial SpA, and the frequency of arthritis was higher in axial SpA patients. Inflammatory markers (ESR and CRP) were statistically higher in FMF with sacroiliitis patients compared with axial SpA and FMF patients.Conclusion When all three groups were compared, the M694V mutation was more common, HLA B27 was largely negative and inflammatory markers were higher in the FMF with sacroiliitis group. FMF should be included in the differential diagnosis of sacroiliitis for managing treatment correctly and preventing complications.
Keywords: FMF with sacroiliitis; axial SpA; FMF; MEFV; HLA B27